Mediators of a Culturally-Sensitive Intervention for Suicidal African American Women - Zhang, Huaiyu (2013)
This study explored intervention outcomes and mechanisms that could help explain why low-income, African American women with a history of intimate partner abuse and suicide attempt improve in response to a culturally-informed intervention, the Grady Nia Project. Specifically, the investigation examined whether or not the intervention had effects on the women and whether or not spiritual well-being and coping mediated the effects of the intervention on suicidal ideation and depressive symptoms. In this randomized controlled clinical trial, data from 89 women who completed both pre- and post-intervention assessments were analyzed. During the post-intervention follow-up, women in the active intervention group reported lower levels of suicidal ideation and depressive symptoms and higher levels of existential well-being and adaptive coping skills than those women randomized to the treatment as usual group. However, only existential well-being was found to mediate treatment effects on suicidal ideation and depressive symptoms. Religious well-being, as well as adaptive and maladaptive coping, did not serve a mediational function. These findings highlight the importance of designing and implementing culturally-sensitive and evidence-based strategies that enhance existential well-being in this population.